Meningkatkan Hasil Belajar Pakat dan Mandiri Melalui Model Discovery Learning Fase F SMA Negeri 1 Siantar Narumonda - Umiar Simarsoit (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The aim of this Classroom Action Research is to find out and measure whether or not the students of class The research subjects were 13 class XI students of SMA N 1 Siantar Narumonda, consisting of 5 men and 8 women. The object of the research is the learning outcomes and student independence in learning Catholic Religion and Ethics in teaching module 1